Study the Effect of Reinforcing Kevlar Fibers with Carbon Fibers and Glass Fibers on the Performance of the Athletic Prosthetic Foot - Talla, Hayder K.; Hassan, Abdul Kareem F.; Oleiwi, Jawad K. (Basrah Journal for Engineering Sciences, 2022)
In this research, the mechanical properties were studied from the experimental, theoretical, and numerical aspects of the sports prosthetic foot for the purpose of providing a sporty prosthetic limb with high performance, easy to use and an appropriate financial cost to use by amputees who have lost their lower limbs (amputation below the knee) in practicing their sports activities and overcoming physical disability. The dimensions of the blades were calculated based on side profiles from European patent specifications. The chosen fibers have high strength, are light in weight, and can be purchased for a lower price than the materials that are used in the production of the sports prosthetic feet that are already on the market and are produced by specialized companies such as Ottobock and Ossur. Six laminates of the composite material consisting of matrix orthocryl lamination 80:20 pro reinforced with different fibers (Kevlar fibers, carbon fibers, glass fibers, and perlon fibers) were fabricated in the form of rectangles using the vacuum system and then cut to the required dimensions using a CNC machine. The density and volume fraction of the samples and the use of the rule of mixtures to calculate the mechanical properties of the laminates were calculated and entered into the ANSYS program. Then the boundary conditions were applied to the athlete’s prosthetic foot and the total deformation, and the total strain energy was calculated to find out the best laminates in the athlete’s foot industry. It was noticed that the laminates reinforced with carbon fibers were better than the laminates reinforced with glass fibers in terms of Young’s Modulus, as well as deformation. The best laminate obtained is (12 K + 4 C).